Comparative study of plasmas obtained by Femtosecond Laser Pulses Ablation in Si and SiO2 - Torchia, Gustavo Adrian (2020)
We analyzed the ablation dynamics for Silicon atoms located in two different environments. Experiments were done with semiconductor (silicon wafer) and a dielectric material (fused silica). We point out some difference in plasma dynamics for Silicon in both environments. Those results can not be explained with current and accepted theoretical models, which asseverate that after the femtosecond laser pulse interact with the surface, the process evolve as metal regardless the kind of material under excitation. Electronic density and temperature were measured with temporal resolution on SiO2 and Si samples by using standard fs LIBS imaging spectroscopy. Extinction time of both plasmas is different depending on the kind of sample under irradiation. Lifetime for plasma obtained in dielectric sample is shorter than that of semiconductor. The main reason to explain this behavior is related to the deep defect induced in the dielectric (fused silica) gap by the femtosecond process; these centers act as sink for the free electron promoted by the laser interaction from the valence band to the plasma, so for dielectrics, shorter lifetime plasmas are obtained when femtosecond pulse irradiation is conducted.